PELATIHAN PEMECAHAN MASALAH UNTUK MENGURANGI GANGGUAN PENYESUAIAN DIRI - Prihartanti, Nanik (Universitas Muhammadiyah Surakarta, 1995)
The satisfying adjustment can be achived if the individual has a problem solving skilll to cope with his tensionn, frustation and conflicts. The problem solving skill can be acquired through training. Besides, one of the determining factors to adjustments is the local culture.The purpose of this study is to find out whether the wayang and the teaching of Suryomentaram as the material of the problem solving training is effective to reduce adjustment disorder. Twenty interested students of the Faculty of Psychology were involved in this study 10 students were the experimental group and the other 10 students were waiting list acted as the control group. The problem solving training was given to the experimental group about two hours per day for three days successicely. The problem solving training was also given to the control group but after the experiment had finished. The effectiveness of treatment was evaluated three times: pre-test, post-test and the follow up (three months later). The measurements used were M.E.test, Self Concept Scale and Live Satisfaction Scale. In addition, they were asked to answer the material and the treatment evaluation questionnaires. The results of this research showed that problem Solving Training could reduce adjustment disorder and it retained after 3 months. Thus it can be effective to reduce adjustment disorder. In this respect, the material of the teaching of Suryomentaram had the biggest aplication value compered with other material in the problem Solving Training to reduce adjustment disorder. It suggests that to deal with the problem of adjustment, the most suitable intervention is something that which is is accordance with the local socio-cultural entities.